From existing conventional building towards LEED certified green building: case study in Bangladesh - Iqbal, Ashik; Jahan, Ismat; Wasiew, Qudrati Al; Emu, Imtiaz Ahmed; Chowdhury, Dipta (Frontiers in Built Environment, 2023)
The construction and operation of buildings have a significant impact on the world's resources and environmental conditions. Green Building refers to the planning, design, construction, and operation of buildings considering indoor environment quality, occupant health, using energy, water, and other resources more efficiently; and reducing waste, pollution, and the overall environmental impact. Among the Green Building guidelines, Leadership in Energy and Environmental Design (LEED) offers a certification and rating system by which buildings are certified in different categories. The LEED rating system is used to rate a building in Bangladesh if it is fulfilling the criteria of Green Building (GB) or not. The research explored how conventional academic building in Bangladesh can be retrofitted to satisfy green building standards. An existing academic building of KUET has been selected for the study. A field survey and Participatory Rural Appraisal (PRA) tools (i.e., Focus Group Discussion (FGD), Key Informant Interview (KII)) were used for the data collection and then the data was analyzed by comparative analysis concerning the LEED 2009 rating system for assessing the building. In the assessment, the New Academic building receives 31 points out of 110 and so cannot earn any certification level. The lacking for which the points were not gained is discussed and the installation of water and energy efficiency features is suggested to earn the green building certification level.